HEALTHCARE POLICY OF GEORGIA AND ACTIVE ENGAGEMENT OF SOCIETY (Globalization and Business, 2023)
The research project “Active Engagement of society in Health care policy” studies hospitals, medical personnel (doctors and nurses) and patients as the main components of Healthcare System in Georgia, targeting two regions Tbilisi and Kutaisi. The initial aim of this research project was to answer the following questions: what is the disposition, viewpoint of the hospital management representatives, medical personnel and patients towards the healthcare policy? What is the level of quality of health services for patients? What is the level of awareness? How actively are different parties involved in the health care system?    The health care policy of Georgia must respond to contemporary challenges and enhance the well-being of the public. Given the relevance of the issue, it is important to study and analyze the public awareness towards the development of a rational health care policy that is focused on delivering competitive medical services. The main novelty of the study is to involve three different stakeholders: hospital management, medical personnel and patients in the research process. Each group has a specific interest and attitude, which in turn determines the degree and extent of their engagement, but each of them proves the need for changes.    The study revealed that patients as the final recipients of medical services are informed about health funding higher than average based on data analysis from both clinics from Tbilisi and Kutaisi (50% of respondents are fully informed, 40% partially informed, and 10% are uninformed). 80% of patients receive information about medical funding directly from their medical staff at a particular place, where they receive health care service. 87.5% of hospital managers are actively involved in the process of change and collaborate with government health legislation.  When it comes to both capital and on-going costs, 87.5% of the funding is spent by mobilizing the internal funds of the clinics, while only 12% comes from complex financing. 83.3% of medical personnel believe that they are involved in the process of clinic’s management and thus in healthcare policy. They generally see the changes to be implemented with the following justifications: improvement of material-technical base of hospitals 8.3%, organizational structure 16.7%, legislative 33.3%, Insurance package optimization for patients 16.7%.  This mandates the need for improvement of legislative and insurance reforms.  Previous studies of Georgia's health care system, consistently demonstrated the satisfaction of beneficiaries of a universal health care program with medical services. This data strongly supports the high level of satisfaction of patients with the quality of received medical services in this study. The data analysis showed that patients' average satisfaction with the quality of medical services is 4.8 out of 5 for both cities.  Despite the increasing satisfaction with quality of medical service for patients, is a subjective process, increasing the risks of medical errors in managing the treatment process. It is imperative to assess the medical risk for both the administration and medical staff. It depends on the prestige of the medical institution and staff and the continued smooth operation of the medical service. Medical risk is directly relevant to patients, so it is advisable to evaluate the impact of various factors on occupational (medical) risk management (R) using multiple regression analyzes within the current data. Exogenous factors are as follows: q1 Demand for the medical profession, q2 Competition in the professional market, q3 Satisfaction with organizational culture and management, q4 Feedback. In this case, the correlation coefficient is 0,876, the coefficient of determination is 0.767, the coefficient of correction - 0.612 and the standard deviation is 0.420. According to the F test, the equation was found to be significant at the 5% significance level.  The equation: R = -2.517 + 0.195q1 + 0.575q2 + 1.195q3-1.080q4  And the standardized equation is: W = 0.117z1 + 0.375z2 + 0.717z3-0.483z4  Factors 2 and 3 in the equation are statistically significant. The signs of regression equation coefficients reflect the subjective attitude towards job risk protection that managers should consider - a competitive environment not generally, but fears of losing particular jobs due to unhealthy approaches, stress on staff, aggravates staffing, or detention or retention conditions.  A successful health care setting must provide improved quality care at lower costs, easily available for patients and developing official feedback system through different settings.  The design of this study was a direct interview method retrospective case control study. Participants were two hospitals in different cities (regions) of Georgia, Tbilisi and Kutaisi. One of them belongs to “Evex medical corporation” and the second one to the network of "Geo Hospitals". Three different types of questionnaires were used for each group (1. For doctors and nurses; 2. For management representatives of the hospital; 3. For patients). Total 40 questions. The most of the conclusions were statistically significant and thus their generalization was possible. The age range of the respondents was 18-70 years; 65% of the respondents were women. Considering the significant difference of each group three different interview questionnaires were used.  The results showed that the part of the society, namely, patients based on received data analysis are generally informed more than average level 0.681 (standard deviation). 50% of the patients say to be completely informed, only 10% of them say that they are not at all aware and 40% say to be moderately aware about the ongoing processes in Healthcare policy in Georgia. 80% of the patients are informed about the health service financing issues from medical personnel at the place of specific medical services. 87.5% of the management representatives from both regions are actively involved in healthcare policy. 88% of total participants of our project expressed their opinion and only 12% avoided commenting towards the desirable changes.    For the evaluation of hospitals’ management were asked whether the management of the clinic is actively involved in health policy, or if the clinic's leadership is trying to change something "contrary to the law", 20% of respondents are trying to be actively involved in health care legislation processes. They are resolving the issue legally, and a similar percentage of respondents are trying to solve the problem with the resources within the clinic.  The difference in the number of patients about the earlier awareness regarding the quality of medical services available in the hospitals is not significant in both cities. The survey shows that most patients at both clinics have prior knowledge of the quality of medical services available at the clinic as to treatment expectation.    A large concern regarding the Georgian health care policy amendments are strongly related with general public health. The results of this study demonstrate a potential positive willingness of three different groups to cooperate and being involved in healthcare system decision making process. This observation in addition adds strength to the continued endorsement of medical professionals that their opinion to be considered while healthcare delivery throughout the country. The findings highlight that 88% of the randomly selected respondents are open for interaction, can express their opinion regarding ​​health care policy, insurance policy; evaluate the quality of health care and financial issues regarding health service and medication, the level of awareness and satisfaction with quality of health services. The study showed that the health care system of Georgia is developing in the directions so that no significant shortcomings are observed. It is noteworthy that reservations are very important for the active involvement of the public. Additional studies are needed to deduce an exact cause and effect relationship between public awareness and healthcare policy management.